2022
DOI: 10.1039/d2sm01198k
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and molecular mobility in renewable semicrystalline copolymers based on polycaprolactone and polyisosorbide

Abstract: A series of novel block copolymers based on two biodegradable polymers, poly(ε-caprolactone), PCL, and poly(isosorbide), PIS, with PIS fractions 5, 10, 25 wr%, are studied herein. The aim is to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Recently, we determined this relationship in a series of renewable copolymers based on PLA 58,65,68 as well as other esters. 57,69 Furthermore, we showed that, for block copolymers, the effects on crystallization related to polymer mobility could be more easily tuned but were stronger when compared with the same polymers in the form of blends. 70…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, we determined this relationship in a series of renewable copolymers based on PLA 58,65,68 as well as other esters. 57,69 Furthermore, we showed that, for block copolymers, the effects on crystallization related to polymer mobility could be more easily tuned but were stronger when compared with the same polymers in the form of blends. 70…”
Section: Introductionmentioning
confidence: 94%
“…56 Deep understanding and mapping of molecular dynamics are extremely useful for polymer-chain topology and interchain associations, which are connected with the performance (mechanical, thermal and electrical conduction, permeability) of materials. 21,35,57,58 The macroscopic performance depends on the crystallinity in a polymer. Among others, the mechanisms of crystallization (i.e., nucleation, chain entanglements, chain folding, spherulitic growth 19,59 ) are strongly connected with the structure and mobility of the polymer chain (length, fragility, diffusion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation